Nutrition management for ischemic stroke patient with hemorrhagic transformation, hemiparesis dextra and dysphagia: A case report - Saliha Puspita Prameswari Fajria; Muharram Nurdin Naufal (BIO Web of Conferences)
This case report details an 81-year-old man with ischemic stroke and hemorrhagic transformation, experiencing decreased consciousness, right-sided paralysis and dysphagia. At risk of malnutrition, the patient required tailored nutritional care and was given low-lactose formula via nasogastric tube (NGT) as initial intervention. Secondary prevention was administered by doctors. Monitoring showed his nutritional intake had not met 80% of his needs. Nevertheless, there were improvements in inflammatory indicators of swallowing ability.